Spherical shock in the presence of an external magnetic field. (March 2016) - Kuramitsu, Y; Matsukiyo, S; Isayama, S; Harada, D; Oyama, T; Fujino, R; Sakawa, Y; Morita, T; Yamaura, Y; Ishikawa, T; Moritaka, T; Sano, T; et al.
Abstract: We investigate spherical collisionless shocks in the presence of an external magnetic field. Spherical collisionless shocks are common resultant of interactions between a expanding plasma and a surrounding plasma, such as the solar wind, stellar winds, and supernova remnants. Anisotropies often observed in shock propagations and their emissions, and it is widely believed a magnetic field plays a major role. Since the local observations of magnetic fields in astrophysical plasmas are not accessible, laboratory experiments provide unique capability to investigate such phenomena. We model the spherical shocks in the universe by irradiating a solid spherical target surrounded by a plasma in the presence of a magnetic field. We present preliminary results obtained by shadowgraphy.